News versus sunspot shocks in a New Keynesian model - Lilia Karnizova (Kiel Institute for the World Economy (IfW), 2010)
Separately, news and sunspot shocks have been shown empirically to be determinants of changes in expectations. This paper considers both of them together in a simple New Keynesian monetary business cycle model. A full set of rational expectations solutions is derived analytically. The analytical characterization allows an explicit comparison of news about future monetary policy and sunspots. The key distinction between the shocks lies in their relation to the realized policy shock. If monetary policy is 'passive', both types of shocks affect model dynamics through forecast errors. The effect of the news on forecast errors is not unique, and the dynamics induced by news and sunspot shocks can be observationally equivalent. If monetary policy is 'active', the sunspots are irrelevant, and the model responses to the news shocks are unique. In both cases, news shocks strengthen the endogenous propagation of the model, since anticipation of future changes prolongs agents' reaction.
Keywords: E32; E47; E52; 330; News shocks; sunspots; expectations; monetary policy; indeterminacy